2007
DOI: 10.1682/jrrd.2006.06.0065
|View full text |Cite
|
Sign up to set email alerts
|

Veterans seeking treatment for posttraumatic stress disorder: What about comorbid chronic pain?

Abstract: Abstract-Our primary aim was to document the rate of comorbidity of physician-diagnosed chronic pain conditions in veterans who were seeking treatment for posttraumatic stress disorder (PTSD). Chronic pain diagnoses (e.g., chronic lowback pain and osteoarthritis) were examined with retrospective chart review. Of the patients with PTSD, 66% had chronic pain diagnoses at pretreatment. These findings are consistent with previous studies that documented the high comorbidity of chronic pain and PTSD using samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
157
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(170 citation statements)
references
References 79 publications
8
157
1
4
Order By: Relevance
“…The high rate of comorbidity between chronic pain and PTSD has been well documented [5,9,[42][43][44], and results from this study are consistent with these prior epidemiologic studies that have identified high prevalence rates of chronic pain and PTSD. Previous literature has demonstrated associations between PTSD and intensified pain severity, disability, and interference [45][46][47]; however, at least one study did not corroborate this finding [4].…”
Section: Outcalt Et Al Veterans With Comorbid Chronic Pain and Ptsdsupporting
confidence: 90%
See 2 more Smart Citations
“…The high rate of comorbidity between chronic pain and PTSD has been well documented [5,9,[42][43][44], and results from this study are consistent with these prior epidemiologic studies that have identified high prevalence rates of chronic pain and PTSD. Previous literature has demonstrated associations between PTSD and intensified pain severity, disability, and interference [45][46][47]; however, at least one study did not corroborate this finding [4].…”
Section: Outcalt Et Al Veterans With Comorbid Chronic Pain and Ptsdsupporting
confidence: 90%
“…Veterans who experience PTSD are likely to experience more intense and disabling pain, more maladaptive thought patterns, and more affective distress, and a provider may need to tailor pain treatment for the patient with comorbid PTSD. At least one study has suggested that treating PTSD may beneficially affect the experience of chronic pain [5]. This highlights the importance of assessing PTSD symptoms when treating Veterans with chronic pain.…”
Section: Outcalt Et Al Veterans With Comorbid Chronic Pain and Ptsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, increased clinical awareness and screening efforts are likely identifying PTSD symptoms among OIF/OEF veterans that might have gone undetected in veterans from previous conflicts. Studies have demonstrated both high levels of PTSD symptom severity among patients with chronic pain [54] and high rates of chronic pain among patients with PTSD [16][17]55]. PTSD symptom severity has been associated with poorer health functioning among OIF/OEF veterans [56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence exists within the scientific literature regarding the co-occurrence of and the relationship between PTSD and chronic pain [11][12][13][14][15][16][17][18]. Otis et al has published a comprehensive summary of theoretical models, including mutual maintenance and shared vulnerability, underlying comorbid chronic pain and PTSD [14].…”
Section: Introductionmentioning
confidence: 99%